ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR TIGA VARIABEL (SPLTV) - Khoirunnisa Khoirunnisa; Rusi Ulfa Hasanah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to determine the mathematical connection ability of class X high school students through SPLTV material. The study was conducted at SMA N 1 Panyabungan Timur class X-MIA1 by taking a sample of 6 research subjects. This research is a research that uses descriptive qualitative method. The instrument used in this study was a test question in the form of a description of 3 questions. The procedure in this study was carried out by analyzing the answers given by students in connecting SPLTV material with other materials and contextual problems which were categorized into three levels of ability, namely high, medium and low. The data analysis technique in this study is to collect data, reduce data and then draw conclusions. The results showed that the mathematical connection ability of students at SMA N 1 Panyabungan Timur was adequate, judging from the results of the tests that had been collected.